Pyrrolyldihydropyrazino[1,2-a]indoletrione Analogue Microtubule Inhibitor Induces Cell-Cycle Arrest and Apoptosis in Colorectal Cancer Cells - Dong-Lin Yang; Hong-Xia Qin; Na-Na Zhang; Ya-Jun Zhang; Jiu-Hong Huang; Chun-Sheng Hu; Xiao-Xue Zhang; Yong Li; Liu-Jun He (Molecules, 2023)
In this study, 2-benzyl-10a-(1H-pyrrol-2-yl)-2,3-dihydropyrazino[1,2-a]indole-1,4,10(10aH)-trione (DHPITO), a previously identified inhibitor against hepatocellular carcinoma cells, is shown to exert its cytotoxic effects by suppressing the proliferation and growth of CRC cells. An investigation of its molecular mechanism confirmed that the cytotoxic activity of DHPITO is mediated through the targeting of microtubules with the promotion of subsequent microtubule polymerisation. With its microtubule-stabilising ability, DHPITO also consistently arrested the cell cycle of the CRC cells at the G2/M phase by promoting the phosphorylation of histone 3 and the accumulation of EB1 at the cell equator, reduced the levels of CRC cell migration and invasion, and induced cellular apoptosis. Furthermore, the compound could suppress both tumour size and tumour weight in a CRC xenograft model without any obvious side effects. Taken together, the findings of the present study reveal the antiproliferative and antitumour mechanisms through which DHPITO exerts its activity, indicating its potential as a putative chemotherapeutic agent and lead compound with a novel structure.